Characteristics of nonsuicidal self-injury associated with suicidal ideation: evidence from a clinical sample of youth. Issue 1 (December 2015) - Victor, Sarah; Styer, Denise; Washburn, Jason
Abstract Background Nonsuicidal self-injury (NSSI) and suicidal ideation (SI) are both distressing and quite common, particularly in youth. Given the relationship between these two phenomena, it is crucial to learn how we can use information about NSSI to understand who is at greatest risk of suicidal thoughts. In this study, we investigated how characteristics of nonsuicidal self-injury related to SI among treatment-seeking adolescents and young adults. Methods Data were collected during routine program evaluation for a self-injury treatment program. Correlations between recent SI and NSSI characteristics were calculated for adolescent and young adult patients (N = 1502). Results Low severity methods of NSSI (e.g. banging) were more strongly associated with SI than high severity methods (e.g. breaking bones). SI was associated with intrapersonal (automatic) NSSI functions. SI was associated with some indices of NSSI severity, such as number of methods and urge for NSSI, but not with others, such as age of onset. Conclusions This study provides a valuable opportunity to expand our knowledge of suicide risk factors beyond those that may apply broadly to self-injurers and to non-injurers (e.g., depression, substance use) to NSSI-related factors that might be specifically predictive of suicidal thoughts among self-injurers. Findings inform clinical risk assessment of self-injurious youth, a population at high risk of suicidal thoughts and behaviors, and provide further insight into the complex NSSI/suicide relationship.